Canadian Expert Panel Recommendations for MRI Use in MS Diagnosis and Monitoring. (21st April 2015) - Traboulsee, Anthony; Létourneau-Guillon, Laurent; Freedman, Mark Steven; O'Connor, Paul W.; Bharatha, Aditya; Chakraborty, Santanu; Girard, J. Marc; Giuliani, Fabrizio; Lysack, John T.; Marriott, James J.; Metz, Luanne M.; Morrow, Sarah A.; et al.
Abstract: Background : A definitive diagnosis of multiple sclerosis (MS), as distinct from a clinically isolated syndrome, requires one of two conditions: a second clinical attack or particular magnetic resonance imaging (MRI) findings as defined by the McDonald criteria. MRI is also important after a diagnosis is made as a means of monitoring subclinical disease activity. While a standardized protocol for diagnostic and follow-up MRI has been developed by the Consortium of Multiple Sclerosis Centres, acceptance and implementation in Canada have been suboptimal. Methods : To improve diagnosis, monitoring, and management of a clinically isolated syndrome and MS, a Canadian expert panel created consensus recommendations about the appropriate application of the 2010 McDonald criteria in routine practice, strategies to improve adherence to the standardized Consortium of Multiple Sclerosis Centres MRI protocol, and methods for ensuring effective communication among health care practitioners, in particular referring physicians, neurologists, and radiologists. Results : This article presents eight consensus statements developed by the expert panel, along with the rationale underlying the recommendations and commentaries on how to prioritize resource use within the Canadian healthcare system. Conclusions : The expert panel calls on neurologists and radiologists in Canada to incorporate the McDonald criteria, the Consortium of Multiple Sclerosis Centres MRI protocol, and other guidance given in this consensus presentation into their practices. By improving communication and general awareness of best practices for MRI use in MS diagnosis and monitoring, we can improve patient care across Canada by providing timely diagnosis, informed management decisions, and better continuity of care. RÉSUMÉ: Recommandations du Groupe consultatif canadien sur l'utilisation de l'IRM pour le diagnostic et la surveillance de la SP. Contexte: Pour poser un diagnostic formel de sclérose en plaques (SP), par opposition à un syndrome isolé au point de vue clinique, une des deux conditions suivantes doit être remplie : une deuxième poussée clinique ou des constatations particulières à l'imagerie par résonance magnétique (IRM), selon les critères de McDonald. L'IRM est également importante après que le diagnostic ait été posé, comme moyen de surveiller l'activité subclinique de la maladie. Bien qu'un protocole standardisé pour le diagnostic et le suivi par l'IRM ait été développé par le Consortium of Multiple Sclerosis Centres, son acceptation et son application ont été sous-optimales au Canada. Méthode: Afin d'améliorer le diagnostic, la surveillance et la prise en charge d'un syndrome isolé au point de vue clinique et de la SP, un Groupe consultatif canadien d'experts a émis des recommandations consensus sur l'application appropriée des critères de McDonald (2010) en pratique clinique, des stratégies pour améliorer la fidélité au Consortium of Multiple Sclerosis Centres MRI protocol standardisé et des méthodes pour garantir la communication efficace entre les professionnels de la santé, particulièrement les médecins référents, les neurologues et les radiologistes. Résultats: Cet article présente huit énoncés de consensus développés par un groupe d'experts ainsi que le fondement de ces recommandations et des commentaires sur la façon de prioriser l'utilisation des ressources dans le cadre du système de santé canadien. Conclusions: Le groupe d'experts invite les neurologues et les radiologistes du Canada à incorporer dans leur pratique les critères de McDonald, le protocole d'IRM du Consortium of Multiple Sclerosis Centres ainsi que les autres directives émises dans le présent consensus. En améliorant la communication et en sensibilisant les professionnels de la santé au sujet de l'utilisation optimale de l'IRM pour le diagnostic et la surveillance de la SP, nous pouvons améliorer les soins aux patients à travers le Canada en établissant un diagnostic rapide, des décisions de traitement éclairées et une meilleure continuité dans les soins prodigués aux patients.